Feasibility of Augmented Reality Integrated E-Comics to Improve Learning Outcomes - Jannah, Rizqa Raudatul; Putra, Galih Mahardika Christian (Mimbar Sekolah Dasar, 2024)
Student learning outcomes that have not been maximized can be caused by one of them is the utilization of learning media that is less varied. The use of varied learning media can attract student interest and can affect student learning outcomes. However, in reality there are still many teachers who have not maximized the use of learning media. The main objective of this research is to develop augmented reality integrated e-comics to improve learning outcomes. The research method used is Research and Development research. The development model used is 4D (Define, design, develop, and disseminate). This study involved teachers and 20 fifth grade students. E-comic integrated augmented reality was developed according to the needs of teachers and students obtained from the results of interviews, observations, and questionnaires. The results showed the percentage level of feasibility of e-comic from media experts obtained a percentage value of 90% with very feasible criteria. Assessment of e-comic integrated augmented reality from material experts obtained a percentage value of 80% with decent criteria. The n-gain test result is 0.581 which shows an increase in student learning outcomes. The conclusion is that e-comic integrated with augmented reality can help students improve learning outcomes in IPAS learning.